Potential uses of volatile fatty acids in soil, water and air - Samaniego-G., José Alfredo (REVISTA TERRA LATINOAMERICANA, 2013)
Volatile fatty acids (VFAs) have biocide, biostatic or toxic effects on microorganisms, plants and animals, depending on their chemical formula and concentration. VFAs are found in soil, water or air, where they can be produced and used. Acetic, formic and propionic acids can be used to preserve food, to fumigate fruit and vegetable, and even reduce or eliminate coliform bacteria from goat´s milk or colostrum of cows. In soil, VFAs could eliminate fungus and bacteria that attack plant roots. Residues of plants or decomposed wastes can generate VFAs, which can be used to produce ethanol or methane. In this study each VFA is discussed in terms of its chemistry, manner of action, uses and potential applications.